Sea-level and reef accretion history of Marine Oxygen Isotope Stage 7 and late Stage 5 based on age and facies of submerged late Pleistocene reefs, Oahu, Hawaii. Issue 1 (January 2014) - Sherman, Clark E.; Fletcher, Charles H.; Rubin, Ken H.; Simmons, Kathleen R.; Adey, Walter H.
Abstract: In situ Pleistocene reefs form a gently sloping nearshore terrace around the island of Oahu. TIMS Th–U ages of in situ corals indicate that most of the terrace is composed of reefal limestones correlating to Marine Oxygen Isotope Stage 7 (MIS 7, 190–245 ka). The position of the in situ MIS 7 reef complex indicates that it formed during periods when local sea level was 9 to 20 m below present sea level. Its extensiveness and geomorphic prominence as well as a paucity of emergent in situ MIS 7 reef-framework deposits on Oahu suggest that much of MIS 7 was characterized by regional sea levels below present. Later accretion along the seaward front of the terrace occurred during the latter part of MIS 5 (i.e., MIS 5a–5d, 76–113 ka). The position of the late MIS 5 reefal limestones is consistent with formation during a period when local sea level was below present. The extensiveness of the submerged Pleistocene reefs around Oahu compared to the relative dearth of Holocene accretion is due to the fact that Pleistocene reefs had both more time and more accommodation space available for accretion than their Holocene counterparts.